The Approaches to the Development of Personnel Management of Schools under the Roman Catholic Diocese of Nakhon Sawan. - Sanghasi, Suwanan; Thongkhamphong, Sunet (Saengtham College Journal, 2022)
The findings of the research indicated that; on the whole, the conditions of the development of personnel management of schools under the Roman Catholic Diocese of Nakhon Sawan seemed to be at the highest level. The schools defined vision, mission and objectives of the personnel management of schools under the Roman Catholic Diocese of Nakhon Sawan, which were not consistent with each school under the Roman Catholic Diocese of Nakhon Sawan. Moreover, the schools lacked adequate manpower; however,the school executives gave precedence to manpower and completely supported teachers and education personnel. For this reason, school executives, teachers and education personnel increasingly understood the problems of manpower. In terms of the problems of the approaches to the development of personnel management of schools under the Roman Catholic Diocese of Nakhon Sawan, it was found that the aspect that the problems were most found was a leave of absence both before and after holidays, including consecutive holidays. A person who can approve a leave of absence considered reasons inappropriately and unnecessarily. In addition, in case a person who requested a leave of absence but cannot hand in a leave letter in person, the approver was always not informed from that person or did not get a leave letter when a leave of absence was approved.